Seleção de conteúdos e diferentes recursos didáticos no ensino fundamental: análise utilizando o tema visão - Fagundes, Laidines Seibel (2016)
This research investigated how science teachers from public schools select topics for teaching the subject the human eye and which teaching resources they used. The second part of the research analyzed the conceptions of the students of the 8th grade of elementary school about the subject. Different teaching resources were applied: the presentation of lecture, three-dimensional model of the eye, exercises with pictures on the computer and practical activities like hole camera . The resource effectivity are evaluated by pre- and post-tests. The presentation of the theme was concluded with the application of a visual acuity test in order to encourage the promotion of health at school. Evaluations revealed the potential of the resources used, and the motivation that these ludic activities provide . These results reinforce the importance and the need to use different methods in elementary school.